2007
DOI: 10.1002/adma.200602215
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evidence for Zn Intersititials in Ferromagnetic Zn1–xCoxO Films

Abstract: The field of spintronics has attracted significant attention since it promises new semiconductor device functionality through functionalization of both electron charge and spin degrees of freedom. Dilute magnetic semiconductors (DMS) which are formed by partial replacement of cations in a nonmagnetic semiconductor by magnetic transition metal ions are promising materials for spintronic devices since they possess charge and spin degrees of freedom in a single substance. [1] Earlier work on Mn-substituted GaAs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
55
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 35 publications
7
55
2
Order By: Relevance
“…Theoretically, Dietl et al first predicted that p-type Mn doped ZnO would show ferromagnetism with T C well above RT [3]. In contrast, Co-doped ZnO was theoretically predicated to become ferromagnetic with n-type doping [4] and a flood of experimental studies of this subject have been reported upon [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, the presented data were plagued by instability and a lack of reproducibility.…”
Section: Introductioncontrasting
confidence: 56%
“…Theoretically, Dietl et al first predicted that p-type Mn doped ZnO would show ferromagnetism with T C well above RT [3]. In contrast, Co-doped ZnO was theoretically predicated to become ferromagnetic with n-type doping [4] and a flood of experimental studies of this subject have been reported upon [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, the presented data were plagued by instability and a lack of reproducibility.…”
Section: Introductioncontrasting
confidence: 56%
“…21,22 Annealing of Zn 1−x Co x O in reducing atmosphere such as in high vacuum, which may produce oxygen vacancies, have been reported to enhance the ferromagnetism, while annealing in oxidizing atmosphere such as air decreases the magnetic moments of Zn 1−x Co x O. [23][24][25][26] In addition, we note that ferromagnetism has been reported in some oxide thin films without magnetic ions, [27][28][29] probably due to defects such as oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…As the temperatures goes down from RT, the magnetization of S2 increases continuously, in agreement with the previous results in DMS thin films. [14,37] Cu doping decreases (increases) the mobile carrier concentration (resistivity), [9,15] detrimental to the formation of conventional threedimensional spin wave. [38] At lower temperatures, both samples exhibit the Curie-Weiss type behavior, suggesting the existence of a paramagnetic phase.…”
mentioning
confidence: 98%
“…[8] The absence of superparamagnetism also manifests in the resemblance between the ZFC and FC curves. [37] Finally, the anomalous feature near 50 K in the M-T curves likely originates from the magnetic transition of oxygen contaminants. [41] The enhanced RTFM was further confirmed by the room-temperature magnetic force microscopy (MFM) measurements.…”
mentioning
confidence: 99%